2019
DOI: 10.1186/s13046-019-1375-9
|View full text |Cite
|
Sign up to set email alerts
|

P53-R273H mutation enhances colorectal cancer stemness through regulating specific lncRNAs

Abstract: Background TP53 is one of the most frequently mutated genes among all cancer types, and TP53 mutants occur more than 60% in colorectal cancer (CRC). Among all mutants, there are three hot spots, including p53-R175H, p53-R248W and p53-R273H. Emerging evidence attributes cancer carcinogenesis to cancer stem cells (CSCs). Long noncoding RNAs (lncRNAs) play crucial roles in maintaining the stemness of CSCs. However, it is unknown if mutant p53-regulated lncRNAs are implicated in the maintenance of CSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 59 publications
(56 reference statements)
1
48
1
Order By: Relevance
“…Loss or mutation of the PTEN gene can lead to accelerated cell proliferation, decreased apoptosis and changes in cell migration and morphology, all of which contribute to tumor formation (Dillon & Miller, 2014). At present, abnormalities in PTEN have been confirmed to be closely related to the development, progression, and prognosis of glioma (Zhang et al, 2019), NSCLC (Shi et al, 2019), breast cancer (Xing et al, 2019), colon cancer (Liu et al, 2019) (Delma et al, 2019;Han, 2019;Zhao et al, 2019). In our study, treatment of SGC-7901 cells with ginsenoside Rg3 significantly increased p53 expression, leading to significant retention of SGC-7901 cells in G1 phase and a high rate of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Loss or mutation of the PTEN gene can lead to accelerated cell proliferation, decreased apoptosis and changes in cell migration and morphology, all of which contribute to tumor formation (Dillon & Miller, 2014). At present, abnormalities in PTEN have been confirmed to be closely related to the development, progression, and prognosis of glioma (Zhang et al, 2019), NSCLC (Shi et al, 2019), breast cancer (Xing et al, 2019), colon cancer (Liu et al, 2019) (Delma et al, 2019;Han, 2019;Zhao et al, 2019). In our study, treatment of SGC-7901 cells with ginsenoside Rg3 significantly increased p53 expression, leading to significant retention of SGC-7901 cells in G1 phase and a high rate of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a murine xenotransplant model these lncRNAs dramatically accelerate tumorigenesis. Their expression is also significantly elevated in colorectal cancer patient tissues that bear R273H mutation in p53 [58].…”
Section: Epithelial-mesenchymal Transition and Related Phenotypesmentioning
confidence: 99%
“… 89 In recent years, more and more studies have shown that lncRNAs are widely involved in DNA methylation, histone modification, chromatin remodeling, and other biological processes in vivo , which can directly interact with transcription factors, functional RNA molecules, and chromatin remodeling modifiers, and regulate the expression of target genes at the epigenetic, transcribed, and post-transcribed levels. 90 , 91 , 92 , 93 In vivo , lncRNAs are mainly used as signaling molecules, bait molecules, guiding molecules, and scaffold molecules to perform biological functions. 94 In addition, some lncRNAs have diversity in the mode of action and can participate in gene expression regulation in a variety of ways at the same time.…”
Section: Main Textmentioning
confidence: 99%